Platelet Aggregate Ratios – Standardization of Technique and Test Results in Patients with Myocardial Ischemia and Patients with Cerebrovascular Disease - Prazich, Julie A.; Rapaport, Samuel I.; Samples, John R.; Engler, Robert (Thrombosis and Haemostasis, 1977)
The technique for measuring platelet aggregate ratios described by Wu and Hoak (1974) was evaluated in normal subjects. The following had no influence upon the test result: age, sex, fasting versu the postprandial state, and the degree of stasis prior to drawing the sample. Variance within subjects was small compared to variance between subjects (0.0009 versus 0.0053, p < 0.01). Platelet aggregate ratios were then measured in 36 patients with coronary artery disease hospitalized with acute chest pain. Their mean platelet aggregate ratio of 0.86 was identical to the mean ratio for 47 normal subjects. Greater variability was found within patients (between samples) than within the normal subjects. This observation raises doubts about the significance of a single measurement of platelet aggregate ratio in such acutely ill patients. Mean platelet aggregate ratios measured daily did not differ over a 7-day period between 11 patients who developed a myocardial infarction and 10 patients who did not. A normal mean platelet ratio was also found on a single measurement from 30 patients with a history of completed stroke (0.87) and from 11 patients with a history of transient ischemic attacks (0.92).